Critical roles of tyrosyl‐DNA phosphodiesterases in cell tolerance to carnosol‐induced DNA damage. (28th April 2020) - Feng, Xiaoyu; Wu, Xiaohua; Wu, Yang; Zhao, Zilu; Xiang, Cuifang; Bai, Xin; Liu, Xin; Zhao, Jingxia; Takeda, Shunichi; Qing, Yong
Abstract: Carnosol is a natural compound with pharmacological action due to its anti‐cancer properties. However, the precise mechanism for its anti‐carcinogenic effect remains elusive. In this study, we used lymphoblastoid TK6 cell lines to identify the DNA damage and repair mechanisms of carnosol. Our results showed that carnosol induced DNA double‐strand breaks (DSBs). We also found that cells lacking tyrosyl‐DNA phosphodiesterase 1 (TDP1), an enzyme related to topoisomerase 1 (TOP1), and tyrosyl‐DNA phosphodiesterase 2 (TDP2), an enzyme related to topoisomerase 2 (TOP2), were supersensitive to carnosol. Carnosol was found to induce the formation of the TOP1‐DNA cleavage complex (TOP1cc) and TOP2‐DNA cleavage complex (TOP2cc). When comparing the accumulation of γ‐H2AX foci and the number of chromosomal aberrations (CAs) with wild‐type ( WT ) cells, the susceptivity of the TDP1 −/− and TDP2 −/− cells were associated with an increased DNA damage. Our results provided evidence of carnosol inducing DNA lesions in TK6 cells and demonstrated that the damage induced by carnosol was associated with abnormal topoisomerase activity. We conclude that TDP1 and TDP2 play important roles in the anti‐cancer effect of carnosol.